Nation branding - Dinnie, Keith (Henry Stewart Talks, 2009)
Objectives of nation branding, Reducing the identity-image gap, Evolution of nation branding, The brand positioning concept, Brand equity, Category flow model of nation branding, Public sector organizations, The brand architecture concept, Nation branding strategy development, Nation brand touchpoints, Ethical issues, Projecting a true and accurate country image